Improving a customer engagement program: action research in strategy implementation - Rossi, Guilherme Viecili (2023)
A Strategic Accounts Management Program is under implementation as part of a larger strategic change in an organization with a challenging context. This study aims to investigate, through action research, what areas of the program would most benefit from a change, plan, implement selected changes, and evaluate the effectiveness of the implemented changes using what is in the light of knowledge in strategy implementation. Initial findings from a survey and subsequent interviews pinpoint three crucial facets requiring refinement within the SAM program. Six months post-implementation, coded interviews reveal positive perceptions among program participants, demonstrating tangible improvements aligned with the research's primary objective.